2012
DOI: 10.1088/1751-8113/45/40/405305
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent decoherence-free subspace

Abstract: With time-dependent Lindblad operators, an open system may have a time-dependent decoherence-free subspace (t-DFS). In this paper, we define the t-DFS and present a necessary and sufficient condition for the t-DFS. Two examples are presented to illustrate the t-DFS, which show that this t-DFS is not trivial, when the dimension of the t-DFS varies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 29 publications
(52 reference statements)
0
23
0
Order By: Relevance
“…Previous papers have used classical physics to calculate and compare the molecular p and large-scale q A components of Π, demonstrating that indeed they of comparable magnitudes (Ingber, 2011(Ingber, , 2012Ingber et al, 2014;Nunez et al, 2013). Also, in the context of quantum mechanics, the wave function of the Π system was calculated, and it was demonstrated that overlap with multiple collisions during the observed long durations of typical Ca 2+ waves (Ingber, 2015;Ingber et al, 2014) support a Zeno effect (Facchi et al, 2004;Facchi and Pascazio, 2008;Giacosa and Pagliara, 2014;Kozlowski et al, 2015;Patil et al, 2015;Wu et al, 2012;Zhang et al, 2014) promoting long coherence times. This approach also suggests some nanosystem-pharmaceutical applications (Ingber, 2015).…”
Section: Introduction To Top-down Premise (Tdp)mentioning
confidence: 89%
“…Previous papers have used classical physics to calculate and compare the molecular p and large-scale q A components of Π, demonstrating that indeed they of comparable magnitudes (Ingber, 2011(Ingber, , 2012Ingber et al, 2014;Nunez et al, 2013). Also, in the context of quantum mechanics, the wave function of the Π system was calculated, and it was demonstrated that overlap with multiple collisions during the observed long durations of typical Ca 2+ waves (Ingber, 2015;Ingber et al, 2014) support a Zeno effect (Facchi et al, 2004;Facchi and Pascazio, 2008;Giacosa and Pagliara, 2014;Kozlowski et al, 2015;Patil et al, 2015;Wu et al, 2012;Zhang et al, 2014) promoting long coherence times. This approach also suggests some nanosystem-pharmaceutical applications (Ingber, 2015).…”
Section: Introduction To Top-down Premise (Tdp)mentioning
confidence: 89%
“…which is the very condition for t-DFSs discussed in Ref. [15]. In other words, when the open quantum system is engineered by an coherent control according to Eq.…”
Section: T) With This Notation the Off-diagonal Block Of The Hamiltmentioning
confidence: 85%
“…Secondly, the evolution of the dynamical invariants I C is governed by Eq. (19). The dynamics of I C is similar to the Markovian-Lindblad master equation with the Lindblad operators B α and the Hamilto-…”
Section: B Decoherence Free Subspace and Dynamical Invariantsmentioning
confidence: 85%